PENGARUH KEPUASAN, NILAI YANG DITERIMA, KEPERCAYAAN, DAN PENGARUH TOKO TERHADAP LOYALITAS GIANT SUPERMARKET - Petra Surya Mega Wijaya; Jessica Stephanie Riyono (Fakultas Bisnis UKDW, 2010)
This study aims to determine the influence of satisfaction,perceived value, trust, and the store affect loyalty in Giant Supermarket. Data on research obtained by distributing questionnaires to the respondents are people who shop at Giant Supermarket. The research method is to use multiple linear regression. From the analysis of data, in this study shows that simultaneous satisfaction variables, perceived value, trust, and store affect influence positive effect on store loyalty. While the partial test showed that the variables of satisfaction, perceived value, and store affect influence positive effect on store loyalty. While the partial variable showed that variable trust has no effect on loyalty. In this study, the most dominant variable of store loyalty is a affect of store variable.Keywords: satisfaction, perceived value, trust, store affect, loyalty, linier multiple regression, Giant Supermarket.